3D printing and amputation: a scoping review. - Ribeiro, Danielle; Cimino, Stephanie R.; Mayo, Amanda L.; Ratto, Matt; Hitzig, Sander L. (Disability & Rehabilitation: Assistive Technology, 2021)
Three-dimensional (3D) printing is an innovative technology being utilized to create prostheses for individuals with limb loss. However, there is a paucity of research on the feasibility of using this technology to fabricate prostheses. A scoping review was conducted to map the literature on 3D printing and its applications in the field of amputation. Using a scoping review framework, a systematic literature search was conducted in three electronic databases (MEDLINE, EMBASE and CINAHL) for all indexed literature up to 29 June 2018. Twenty-eight articles met the inclusion criteria. The majority of studies had small sample sizes (five participants or less; n = 20) and used a case study design (n = 17). The benefits of 3D printing technology include higher levels of customization and lower production costs. However, the functionality of 3D printed prostheses is lacking. There is also a need for more robust research designs to obtain a better understanding of the advantages and disadvantages of 3D printed prostheses and its impact on end-user outcomes. The use of 3D printing technology has a number of benefits for improving the manufacturing process of devices for people with lower and upper limb loss. However, more research and technological advancements are required to fully understand the impact of this technology on patients and how it will affect their daily life. The long-term effects of this technology will also need to be investigated in order to produce a more sustainable alternative to traditional prostheses. The use of 3D printing technology for the fabrication of prosthetics for persons with limb-loss has a number of promising features to improve the fitting and customization of these devices for this patient population. Although the costs of producing 3D printed devices is less expensive and burdensome than traditional approaches to manufacturing techniques, there is a need for additional technological advancements to improve the functionality of these devices. Future research needs to adopt more robust research designs with larger sample sizes to provide a better understanding of the viability of using 3D printing technology to improve patient outcomes.